Statistical Analysis of Air Pollution and Life Expectancy in Eastern Europe - DINU, Cristian; POPÎRLAN, Cristina; TUDOR, Irina Valentina (Journal of Environmental Management and Tourism; Vol 11 No 3 (2020): JEMT Volume XI Issue 3(43) Summer 2020DO - 10.14505//jemt.v11.3(43).30, 2020)
In this paper, we present a statistical analysis of the main air pollutants and life expectancy in some countries from Eastern Europe: Bulgaria, Czech Republic, Hungary, Poland, Romania and Slovakia. We use statistical tools to describe and model air pollution data. The data involve a period of 18 years and include the annual average concentrations volatile organic compound, particulate matters, nitrogen oxides (NO X ), sulphur oxides (SO X ). The descriptive analysis of these variables is presented, before the model of the dependence between them, in order to discover the relationship between them. The correlation and regression analysis allow to find precisely formula of the connections that link life expectancy (LE) and the main air pollutants. The results obtained in this study reveals a new perspective of health and air quality and also, they present a new tool for all national and international agency for arguing that reducing the air pollution is closely related to a long-life expectancy.